Quality of life in geriatric patients [Geriatrik Hastalarda Yaşam Kalitesi] - (:unkn) unknown (My University, 2006)
The average life span of people has been increasing dramatically in all around the world. The aging of the world population causes major health and socioeconomic problems. There are two models define health and illness. The first is the biomedical model, and the other is the quality-of-life model. The biomedical model is the most familiar model to physicians which is the basis for many of the advances in medicine that have occurred during the last 100 years and is most useful for unicausal processes. However disability in the geriatric population is often multicausal. On the other hand "the quality-of-life model", focuses on function and well-being. It is most useful for understanding complex behaviors and is derived from the fields of social science, psychology, and economics. The quality of life concept becomes the corner stone in providing the optimal health care and quality of life measures will assume increasing importance in the field of rehabilitation. The increase in average life span is an important goal but the more important is to maintain the quality of life in also older ages. Providing productive and healthy life for elderly has to be main goal for health care professionals and there are lots of things to do for reaching these goals.
Keywords: Elderly; Quality of life